Treatment of Charcot Neuroarthropathy and osteomyelitis of the same foot: a retrospective cohort study - Martin Berli; Lazaros Vlachopoulos; Sabra Leupi; Thomas Böni; Charlotte Baltin (BMC Musculoskeletal Disorders, 2017)
Abstract Background We evaluated treatment of osteomyelitis in the foot in the presence of Charcot neuroarthropathy, a devastating condition with progressive degeneration and joint destruction. We hypothesized that there was a difference in (1) amputation rate, (2) amputation level, (3) duration of antibiotic therapy, and (4) duration of immobilization for treatment of osteomyelitis within versus outside the Charcot zone. Methods Forty patients (43 ft) diagnosed with Charcot neuroarthropathy and osteomyelitis of the same foot were retrospectively analyzed. Some patients were successfully treated for osteomyelitis at different sites on the same foot at different times, thus 60 cases of osteomyelitis were identified in 40 treated patients. Cases were divided according to osteomyelitis localization: Group 1 had osteomyelitis outside the active Charcot region; Group 2 had osteomyelitis within the active Charcot region. Results Male patients (n = 29; mean age 58.2, range 40.1 to 77.5 years) were younger than female patients (n = 11; mean age 70.4, range 51.4 to 87.5, p = 0.02 years). Amputation rate was 52% overall (26/40 patients; 26/43 ft): 63% of 30 Group 1 cases and 40% of 30 Group 2 cases (p = 0.09). Amputation level (p = 0.009), duration of antibiotic treatment (p = 0.045) and duration of immobilization (p = 0.01) differed significantly between the groups. Conclusions Osteomyelitis within the Charcot region is associated with a higher level of amputation and longer durations of antibiotic therapy and immobilization. Osteomyelitis outside and within the Charcot affected region should be considered separately. If osteomyelitis occurs outside the active Charcot region, primary amputation may be preferred to internal resection. Level of Evidence Retrospective cohort chart review study.